Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1111/jgh.16243
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive predictive models based on lifestyle analysis and risk factors for early‐onset colorectal cancer

Abstract: BackgroundColorectal cancer (CRC) incidence has increased among patients aged <50 years. Exploring high‐risk factors and screening high‐risk populations may help lower early‐onset CRC (EO‐CRC) incidence. We developed noninvasive predictive models for EO‐CRC and investigated its risk factors.MethodsThis retrospective multicenter study collected information on 1756 patients (811 patients with EO‐CRC and 945 healthy controls) from two medical centers in China. Sociodemographic features, clinical symptoms, medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Moreover, other findings identified within this seminal study were that 70.1% of tumors were located distal to the descending colon, and with 40% being also node-positive, while 20% of EOCRC cases also having microsatellite instabilities [11]. Another highly informative study was conducted by Deng and colleagues earlier in 2023, which focused on developing noninvasive predictive models for EOCRC, based mainly upon lifestyle analyses and other identified risk factors [12]. The results of this particular study, conducted over 811 EOCRC patients and 945 healthy controls, concluded that the consumption of sweet/fried foods items at a frequency of over thrice-weekly, was highly linked to EOCRC manifestation [12].…”
Section: Introductionmentioning
confidence: 78%
“…Moreover, other findings identified within this seminal study were that 70.1% of tumors were located distal to the descending colon, and with 40% being also node-positive, while 20% of EOCRC cases also having microsatellite instabilities [11]. Another highly informative study was conducted by Deng and colleagues earlier in 2023, which focused on developing noninvasive predictive models for EOCRC, based mainly upon lifestyle analyses and other identified risk factors [12]. The results of this particular study, conducted over 811 EOCRC patients and 945 healthy controls, concluded that the consumption of sweet/fried foods items at a frequency of over thrice-weekly, was highly linked to EOCRC manifestation [12].…”
Section: Introductionmentioning
confidence: 78%
“…There are two main categories of risk models for predicting CRC or AN based on their predictor features: (1) conventional risk model, which uses known and well-established risk factors for CRC; and (2) composite model, which combines well-established risk factors with more advanced features, such as test/laboratory findings and genetic factors. Among the 41 included studies, we identified 22 original conventional risk models, [36][37][38]40,45,48,50,51,53,54,58,59,61,[63][64][65][67][68][69][70]72,74] and 13 composite models [39,[41][42][43][44]47,56,57,62,71,73,75,76]. Of these, three conventional risk models have undergone external validation in separate studies: (1) the Asia-Pacific Colorectal Screening (APCS) model [45], validated in four other studies [46,49,66,70];…”
Section: Characteristics Of Risk Prediction Models For Crcmentioning
confidence: 99%
“…The newly developed risk prediction models between 2011 and 2021 predominantly originated from Asian countries (n = 19), including China [37,46,68,74], Korea [47,48,50,51,61,62,66,70,72], Japan [59,65], Thailand [57], Hong Kong [45,49], and Taiwan [56]. Among these novel risk prediction models based on Asian populations, the most common predictors were age (n = 19), smoking history (n = 17), sex (n = 15), BMI (n = 14), family history of CRC (n = 14), alcohol intake (n = 8), and diabetes mellitus (n = 6) [37,[45][46][47][48][49][50][51]56,57,59,61,62,65,66,68,70,72,74,80].…”
Section: Risk Predictors For Asian Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The established causative genes include PRRT2, KCNQ2, SCN1A, SCN2A, STXBP1, CDKL5, and ARX. In addition, structural anomalies including neuronal migration disorder or dysgenesis are often associated (Song et al, 2021). Mutations in Nitrogen Permease Regulator Like-2 (NPRL2) are being recognized increasingly as a major player in producing brain structural anomalies (Sun et al, 2021).…”
Section: Introductionmentioning
confidence: 99%